2000
DOI: 10.1177/107906320001200302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perpetration Characteristics Between Male Juvenile and Adult Sexual Offenders: Preliminary Results

Abstract: This study investigated the characteristics of the sexual abuse perpetrated by 16 juvenile (JSO) and 19 adult sexual offenders (ASO). Data were collected from a randomly selected group of males who received psychotherapy services at a community agency. The results revealed significant differences between the JSOs and the ASOs on the number of committed offenses, length of sexual relationships maintained with victims, quality of these relationships, nature of the sexual acts committed, and presence of force dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…Offender age was dichotomized for the purpose of the present study. This is consistent with the current legal definition for adolescent and adult offenders as well as with previous research Kaufman et al, 1998;Miranda & Corcoran, 2000). More specifically, the present study will dichotomize offenders' by age, considering offenders who committed CSA prior to the age of 18 as an adolescent and offenders who committed CSA at or later than the age of 18 as adults.…”
Section: Descriptions and Measurement Of Study Constructssupporting
confidence: 64%
See 2 more Smart Citations
“…Offender age was dichotomized for the purpose of the present study. This is consistent with the current legal definition for adolescent and adult offenders as well as with previous research Kaufman et al, 1998;Miranda & Corcoran, 2000). More specifically, the present study will dichotomize offenders' by age, considering offenders who committed CSA prior to the age of 18 as an adolescent and offenders who committed CSA at or later than the age of 18 as adults.…”
Section: Descriptions and Measurement Of Study Constructssupporting
confidence: 64%
“…In an attempt to address this gap in the literature, Miranda and Corcoran (2000) explored this issue and found that adolescent CSA offenders were more likely to utilize force in the commission of their abusive acts than their adult counterparts.…”
Section: Offender Agementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, literature pertaining to sex offending generally suggests important differences between these two groups (Miranda & Corcoran, 2000). To increase validity, a range of sources was included.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Além do foco e das técnicas utilizadas na intervenção, estudos têm discutido sobre a faixa etária do agressor, suas características de personalidade e tipo de interação sexual, que envolvia suas ações, como aspectos importantes de serem considerados ao propor atendimento (Edward & Beech, 2004;Miranda & Corcoran, 2000). Observar esses aspectos pode auxiliar os profissionais a ajustarem os objetivos da proposta de atendimento, bem como avaliar potenciais riscos, como, por exemplo, abandono do tratamento ou reincidência, principalmente quando se trabalha com adolescentes (Edward & Beech, 2004).…”
Section: Atendimento a Mães E Abusadoresunclassified